The proverbs as mirror of the Vhavenda culture and philosophy - Khuba, Asnath Elelwani (My University, 1985)
Refer to the document
Thesis (M.A. (African Languages)) --University of the North, 1985
Keywords: Venda language; Proverbs; Venda culture; Venda language -- Criticism and interpretation; Venda language -- Proverbs; Venda language -- Social aspects